Compendium: Knowledge economy practices in the world of information technologies - Donon, Yann Pierre (Serbian Journal of Management, 2019)
This paper treats the positioning of top level management towards the Information Technology (IT) departments in a company at the age of cloud computing. The conceptual knowledge needed by the management to make profitable decisions regarding IT, take financial opportunities of professional clouds technologies, what to take in account for a migration towards a new infrastructure and what tools can be used for realistic costs estimation will be overseen. This is paper is addressed not to technicians but decisional chains having little or no knowledge about cloud and general IT technologies, needing to make strategic decisions or needing to get a better understanding over their IT environment.